The Village Government’s Strategy In Handling Stunting In Uwen Pantai Village, Taniwel Timur District, Seram Bagian Barat Regency - Mananuwe, Prisilia; Warbal, Montgomery; Renyut, Bernard C. (JIMAD : Jurnal Ilmiah Multidisiplin, 2025)
This research aims to analyze the strategy for stunting prevention and management in Uwen Pantai Village, Taniwel Timur District, West Seram Regency, based on Presidential Regulation No. 72 of 2021 concerning the acceleration of stunting reduction. The research method used is descriptive qualitative with data collection through interviews, observations, and documentation. The findings show that the implementation of stunting prevention strategies in the village is supported by several key elements: the existence of a well-organized integrated team, community involvement, and cross-sector collaboration. However, challenges remain, such as limited health facilities, lack of public awareness, and insufficient budget allocation. The local government and village apparatus have made efforts through nutrition counseling, provision of supplementary food, and health service outreach. The study concludes that although the strategy is in line with the national framework, there is a need for improvement in inter-sectoral coordination, capacity building for local health workers, and the use of accurate data for program planning. It is recommended that further research focus on the role of community empowerment in sustaining stunting prevention programs in rural and remote areas.